Lateral Meniscus Posterior Root Lesion Influences Anterior Tibial Subluxation of the Lateral Compartment in Extension After Anterior Cruciate Ligament Injury. Issue 4 (March 2020) - Zheng, Tong; Song, Guan-yang; Feng, Hua; Zhang, Hui; Li, Yue; Li, Xu; Zhang, Zhi-jun; Ni, Qian-kun; Feng, Zheng
Background: The lateral meniscus posterior root (LMPR) lesion further decreases dynamic knee stability after anterior cruciate ligament (ACL) injury owing to the loss of the "wedge effect" maintained by the posterior horn of the lateral meniscus. However, the effect of LMPR lesions on the static tibiofemoral relationship in extension after ACL injuries is not determined. Purpose: To (1) determine the effect of LMPR lesions on anterior tibial subluxation of the lateral compartment (ATSLC) in extension in patients with ACL injuries and to (2) identify the LMPR-related factors associated with excessive ATSLC in extension. Study Design: Cohort study; Level of evidence, 3. Methods: Between January 2015 and December 2017, 405 consecutive patients with diagnosed ACL injuries who underwent primary ACL reconstructions were retrospectively reviewed. Among them, 45 patients with combined ACL injuries and LMPR lesions (ACL+LMPR group) and 51 patients with isolated ACL injuries (ACL group) were identified. Values of ATSLC in extension were measured on preoperative supine magnetic resonance imaging and classified into high grade (≥6 mm) and low grade (<6 mm). The mean ATSLC in extension and the proportion of patients with high-grade ATSLC in extension were compared between the groups by univariate analysis. In the ACL+LMPR group, predictors of high-grade ATSLC in extension—including age, sex, body mass index, affected side, cause of injury, period from injury (<12 or ≥12 weeks), LMPR lesion pattern (radial tear or root avulsion), and meniscofemoral ligament integrity (intact or impaired)—were assessed by univariate analysis and multivariate logistic regression analysis. Results: The mean ATSLC in extension in the ACL+LMPR group was significantly greater than that in the ACL group (5.6 mm vs 3.1 mm; P = .001). The proportion of patients with high-grade ATSLC in extension in the ACL+LMPR group was also significantly larger than that in the ACL group (44.4% vs 15.7%; P = .002). In addition, the root avulsion (instead of radial tear) (odds ratio, 28.750; 95% CI, 2.344-352.549; P = .009) and the period from injury ≥12 weeks (odds ratio, 17.095; 95% CI, 1.207-242.101; P = .036) were determined to be the 2 independent predictors of high-grade ATSLC in extension. However, age, sex, body mass index, affected side, cause of injury, and meniscofemoral ligament integrity were not. Conclusion: After ACL injuries, concomitant LMPR lesion further increased ATSLC in extension. Chronic LMPR avulsion was associated with high-grade ATSLC in extension.